Fracture Resistance of Repaired 5Y-PSZ Zirconia Crowns after Endodontic Access - Andreas Greuling; Mira Wiemken; Christoph Kahra; Hans Jürgen Maier; Michael Eisenburger (MDPI AG, 2023)
This study analyzed the fracture load before and after a chewing simulation of zirconia crowns that were trepanned and repaired using composite resin. Overall, 3 groups with 15 5Y-PSZ crowns in each group were tested. For group A, the fracture load of the unmodified crowns was evaluated. For group B, the crowns were trepanned and repaired using composite resin, also followed by a fracture test. For group C, crowns were prepared like in group B but received thermomechanical cycling before the final fracture tests. Furthermore, scanning electron microscopy (SEM) and X-ray microscopy (XRM) analysis were performed for group C. The mean fracture loads and standard deviation were 2260 N ± 410 N (group A), 1720 N ± 380 N (group B), and 1540 N ± 280 N (group C). Tukey-Kramer multiple comparisons showed a significant difference between groups A and B (p < 0.01) and groups A and C (p < 0.01). After ageing, surface fissures were detected via SEM, but no cracks that reached from the occlusal to the inner side of the crown were detected via XRM. Within the limitations of this study, it can be stated that trepanned and composite-repaired 5Y-PSZ crowns show lower fracture loads than 5Y-PSZ crowns without trepanation.